A universal modified LMS algorithm with iteration order hybrid switching. (March 2017) - Cheng, Songsong; Wei, Yiheng; Chen, Yuquan; Liang, Shu; Wang, Yong
Abstract: This paper presents a fractional order modified least square algorithm(FOMLMS), which involves an iteration order switch strategy. A FOMLMS scheme whose iteration order can be extended into α ∈ ( 0, 2 ) is investigated. The performance of FOMLMS with the iteration order in different interval ( 0 < α < 1 or 1 < α < 2 ) is separately analyzed. It turns out that, both of a larger iteration order ( 0 < α < 2 ) and iteration step size can always result in a faster response speed and convergence speed. Therefore, in order to obtain a satisfying convergence speed without sacrificing other performance, a hybrid switch law of iteration order is naturally developed. Finally, the validity of this proposed algorithm is illustrated by three numerical examples. Abstract : Highlights: A fractional order modified least square algorithm (FOMLMS) with (0<α<2) is proposed. The performance of FOMLMS with α in two interval (0<α<1 or 1<α<2) is separately analyzed. A hybrid switch law of α is developed to obtain a better convergence speed.